Teacher Support and Students’ Academic Resilience in Universal Secondary Education Schools in Luwero District, Uganda - Justine Nansamba; Wilson Mugizi; Joseph Rwothumio; Joshua Kimata Kato (Interdisciplinary Journal of Education)
This study investigated the impact of teacher support on students' academic resilience in Universal Secondary Education schools in Luwero district, Uganda. Specifically, the study examined whether teacher investment of effort, positive regard, and accessibility significantly influenced students' academic resilience, defined as perseverance, help-seeking, and positive affect. Using a quantitative approach and correlational research design, the study surveyed 324 students selected through simple random sampling. Data collection employed a self-administered questionnaire, and analysis involved structural equation modelling (SEM) using SmartPLS. The results revealed that teacher investment of effort, positive regard, and accessibility had a positive and statistically significant impact on students' academic resilience. The findings suggest that teacher support, particularly positive regard, followed by investment of effort and accessibility, fosters students' academic resilience. The study recommends that head teachers sensitise teachers to provide comprehensive support by creating a supportive learning environment that involves being invested in students' academics, accessible, and showing positive regard. This study's practical contribution lies in demonstrating how teacher support can promote students' resilience, providing valuable insights for educators and policymakers.